1991
DOI: 10.1002/cm.970200407
|View full text |Cite
|
Sign up to set email alerts
|

The calcium‐induced curvature reversal of rat sperm is potentiated by cAMP and inhibited by anti‐calmodulin

Abstract: Rat sperm, demembranated with 0.1% Triton X-100, were used to explore the reversal in flagellar curvature induced by calcium ion. As reported earlier (Lindemann and Goltz, Cell Motil. Cytoskeleton, 10:420-431, 1988), the radius of curvature of the flagellar midpiece of rat sperni is controlled by the free Caz+ concentration. A reversal of the direction of curvature (judged by the asymmetric sperm head) takes place at --2.5 X lop6 M free Ca2In our current study, the time course of the curvature change, after el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Further studies will determine which of the several NHE systems are functionally coupled to the Na,K-ATPase a4 isoform. Changes in pH have been shown to influence sperm motility, and in detergent-extracted preparations of rat sperm, variations in the proton concentration have been shown to modulate sperm flagellar bending pattern and its response to cAMP and Ca 2C (Lindemann et al 1991). Therefore, regulation of the proton concentration in the cells may represent one of the mechanism by which the Na,K-ATPase a4 isoform influences sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will determine which of the several NHE systems are functionally coupled to the Na,K-ATPase a4 isoform. Changes in pH have been shown to influence sperm motility, and in detergent-extracted preparations of rat sperm, variations in the proton concentration have been shown to modulate sperm flagellar bending pattern and its response to cAMP and Ca 2C (Lindemann et al 1991). Therefore, regulation of the proton concentration in the cells may represent one of the mechanism by which the Na,K-ATPase a4 isoform influences sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperactivated motility pattern can be initiated in demembranated sperm by raising free Ca 21 levels from the range of pCa > 7 up to pCa 4 to 5 (Lindemann and Goltz, 1988;Lindemann and Kanous, 1989;Lindemann et al, 1991;Ishijima et al, 2006).…”
Section: Consequences Of Anatomy On Motilitymentioning
confidence: 99%
“…We now know that this conversion of the beating pattern requires the entry of Ca 21 for its initiation (Suarez and Osman, 1987) and maintenance (Carlson et al, 2009). The hyperactivated motility pattern can be initiated in demembranated sperm by raising free Ca 21 levels from the range of pCa > 7 up to pCa 4 to 5 (Lindemann and Goltz, 1988;Lindemann and Kanous, 1989;Lindemann et al, 1991;Ishijima et al, 2006).The greatly increased amplitude of the beat during hyperactivated motility necessitates that greater flagellar curvature is achieved, particularly in the midpiece. This is accompanied by greater sliding displacements of the doublets especially in the proximal part of the flagellum (Ishijima, 2007;Kaneko et al, 2007).…”
mentioning
confidence: 99%
“…In addition to the role of phosphorylation signalling in sperm motility, studies with a variety of species have shown that Ca 2+ ions play a key role in the development and maintenance of sperm progressive motion and hyperactivation (Lindemann et al, 1991;Serres et al, 1991;Marin-Briggiler et al, 1999;Marin-Briggiler et al, 2003;Marquez and Suarez, 2004). Using demembranated sperm models, some of these investigations have revealed that Ca 2+ levels modulate the waveform of the sperm tail (Ho et al, 2002;Lindemann and Goltz, 1988).…”
mentioning
confidence: 99%